Fourier Transformation Infrared Spectroscopic Studies of Acidity of NaH-13 X Zeolites - Sofy, Shatha Abd-Alhameed Al. (Al-Nahrain Journal for Engineering Sciences, 2018)
Fourier transformation Infrared spectroscopy (FTIR) has been used to characterize and measure the concentration of acid sites (Si-OH-Al groups) in NaH-13 X Zeolites. Ion exchange was followed by dealumination to get (28, 40, 65, 85.8 and 97.5 Wt. %) of NaH-13 X Zeolites samples. The conclusion of homogeneity of OH groups was obtained by analysis of Fourier transformation infrared spectroscopy absorption bands of OH groups after adsorption and desorption of Ammonia. It found that there were different acid sites on a broader absorption (3,800-3,000 cm-1) corresponds to hydroxyl groups of the less acidic Brønsted acid sites approximately at 3464cm-1 and the more acidic at 3441cm-1 and Lewis acid sites was found at 1636 cm-1 which is few and weak acid sites . It can be conclusion that concentrations of OH groups increased with increasing the exchange degree and delamination. The concentration of acid sites in samples were calculated from stretching frequencies and extinction coefficients of OH bands, also the frequency shift ??OH = 23 cm-1 which was due to the hydrogen bonding of OH groups with ammonia in 97.5 % NaH-13 X Zeolites. Knowing the acidity of catalyst is important for the reactions which required acidic surface.